Cannabis use among cancer survivors in the United States: Analysis of a nationally representative sample. Issue 21 (20th July 2021) - Do, Elizabeth K.; Ksinan, Albert J.; Kim, Sunny Jung; Del Fabbro, Egidio G.; Fuemmeler, Bernard F.
Abstract : Background: Research on cannabis use among those with a history of cancer is limited. Methods: Prevalence of past‐year cannabis use among individuals with and without a cancer history and predictors of use within these 2 groups were determined using data from the Population Assessment of Tobacco and Health study, a nationally representative, longitudinal survey conducted in the United States (waves 1‐4; 2013‐2018). Discrete time survival analyses were used to estimate baseline (wave 1) predictors (physical health status, mental health status, pain, and demographic variables) on past‐year engagement with cannabis within individuals who reported a cancer diagnosis at wave 1 (n = 1022) and individuals who reported never having cancer at any wave (n = 19, 702). Results: At the most recent survey, 8% of cancer survivors reported past‐year cannabis use, compared with 15% of those without a cancer history. Across 4 time points, an estimated 3.8% of cancer survivors engaged with cannabis, as compared to 6.5% of those without a cancer history. Across both groups, older age and having health insurance were associated with lower likelihood of engaging in cannabis use, whereas greater levels of pain were associated with higher likelihood of engaging in cannabis use. Among those without a cancer history, being female, White, and having better mental health status were associated with lower likelihood of engaging in cannabis use. Conclusions: Although cannabis use prevalence is lower among cancer survivors, the reasons for use are not markedly different from those without a cancer history. Continued monitoring of use, reasons for use, and harms or benefits is warranted. Lay Summary: Results from this study, which uses data from the Population Assessment of Tobacco and Health Study, indicate that cannabis use is generally increasing across cancer survivors and those without a history of cancer. Cancer survivors are using cannabis at slightly lower rates than those without a history of cancer. Factors related to pain seem to be more prevalent in cancer populations relative to the general population, and could be contributing to cannabis use within cancer survivor populations. Abstract : Although cannabis‐use prevalence is lower among cancer survivors, reasons for use are not markedly different from those without a cancer history. The continued monitoring of use, the reasons for use, and the harms or benefits of cannabis use is warranted.